2016
DOI: 10.1007/s12291-016-0582-9
|View full text |Cite
|
Sign up to set email alerts
|

Status of Serum Calcium, Vitamin D and Parathyroid Hormone and Hematological Indices Among Lead Exposed Jewelry Workers in Dhaka, Bangladesh

Abstract: Jewelry utilizes lead either directly or as a base metal. Costume jewelry requires lead before molding and plating the product with valuable metals. Therefore, such ornaments have a great potential to release heavy metals having health hazards. Also, jewelry makers engaged in preparing German silver, an alloy, apply lead in smelting, alloying, rolling and milling silver wires and pieces. The metal is taken up by blood, soft tissues and bone. The biological effects of lead are dependent upon the level and durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The ZPP concentration has been commonly used in clinical diagnosis of chronic occupational lead exposure [ 52 54 ]. Mazumdar et al [ 55 ] showed that ZPP levels are negatively correlated with serum calcium concentration in jewelry makers (PbB: 69 μ g/dl). Our observation suggests that low calcium levels may enhance the negative impact of lead on heme biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The ZPP concentration has been commonly used in clinical diagnosis of chronic occupational lead exposure [ 52 54 ]. Mazumdar et al [ 55 ] showed that ZPP levels are negatively correlated with serum calcium concentration in jewelry makers (PbB: 69 μ g/dl). Our observation suggests that low calcium levels may enhance the negative impact of lead on heme biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed with the strong negative association between BPbLs and serum 25(OH)D levels (PND21; β = −0.64, R 2 = 0.47, p < 0.0001 and PND30; β = −0.78, R 2 = 0.25, p < 0.01) in all rat pups of the same age ( n = 31) irrespective of Pb exposure group. Few epidemiological studies have reported similar significant negative associations between Pb and serum 25(OH)D among women [ 49 ], Pb-exposed workers [ 20 , 21 ] and children [ 22 , 25 ]. Kersey et al [ 50 ] have found negative but statistically insignificant, association between BPbls and serum 25(OH)D levels in healthy toddlers and children under 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that high Pb exposure is one of the potential risk factor of VDD [ 20 , 21 ]. Studies of children with high Pb exposure demonstrated a significant negative association between 1,25-dihydroxyvitamin D [1,25(OH) 2 D] concentration and blood Pb level (BPbL) [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Serum calcium level is maintained under tight homeostatic control and directly and indirectly involves the influence of diverse roles played by parathyroid hormone (PTH), vitamin D and phosphate. 7 Magnesium (Mg), may also be added to the group because it remotely plays a fundamental role in the release and action of PTH and controls many calcium channels, making it indispensable in Ca metabolism. 8 The close and complex association between Pb and Ca metabolism has been recognized for years.…”
Section: Introductionmentioning
confidence: 99%